Sequential saccharification and simultaneous fermentation (SSSF) of sago hampas for the production of bioethanol - Micky Vincent; Berry Rence Anak Senawi; Ennry Esut; Norizawati Muhammad Nor; Dayang Salwani Awang Adeni (Universiti Kebangsaan Malaysia, 2015)
Bioethanol is a very environmentally friendly liquid biofuel that is not only renewable, but also sustainable. It is currently deemed as a highly suitable additive and substitute energy source to replace fossil based fuel. In this study, bioethanol was produced from sago hampas by using commercial amylase, cellulase and Saccharomyces cerevisiae via sequential saccharification and simultaneous fermentation (SSSF), a modified version of the simultaneous saccharification and fermentation (SSF) process. SSSF was performed on sago hampas at 2.5 and 5.0% (w/v) feedstock load for five days. The samples taken from the SSSF broths were analysed via high performance liquid chromatography (HPLC) for ethanol, glucose and acetic acid production. From the results obtained, SSSF with 5.0% sago hampas loading exhibited the highest ethanol production at 14.13 g/L (77.43% of theoretical ethanol yield), while SSSF using 2.5% sago hampas loading produced ethanol at 6.45 g/L (69.24% of theoretical ethanol yield). This study has shown that ethanol not only can be produced from sago hampas using different enzyme mixtures and S. cerevisiae via SSSF, but yields were also high, making this process highly promising for the production of cheap and sustainable ethanol as fuel.